Using the principles of precision animal husbandry in fishbreeding - Stündl, László; Fehér, Milán; Bársony, Péter (Acta Agraria Debreceniensis, 2012)
Aquaculture species such as fish, crayfish, molluscs and plats are a wide range of products, with continuously growing demand worldwide. The reasons for this is that they are cheap and easy-toraise protein sources, thus having significance in food supply especially in developing countries in tropic regions, moreover, the premium category foodstuffs in developed high income countries are also belonging to this category. World annual total production of 164 million tons (2009) are made up of two sources: 1) marine and inland fisheries landings that are stagnating for several years and 2) aquaculture which is growing dynamically with annual 6% rate between 2000–2009. The latter is accounting for nearly 45% of the total supply due to the depleting marine stocks caused by overfishing. Aquaculture is growing continuously also because the production is safe and can be planned well. Intensive fish production systems are the representatives of precision animal production, several types exist and widespread worldwide. The modern computerized temperate water recirculation plants with several thousand m3 capacity are widespread also in Europe because they make it possible to produce even the most valuable species whole year round. A key issue in the technical/feeding outlay is to meet the demands of the cultured species the best and the operation of the system is to be safe and cost-effective. One condition for this is intensification: enable to produce more product per unit resource input or effort. The facilities need significant amount of energy, thus renewable energy sources are to be favoured for which Hungary has comparative advantages.